Enhanced resistance to helium irradiations through unusual interaction between high-entropy-alloy and helium. (15th April 2023) - Cheng, Tao; Wei, Guo; Jiang, Shengming; Zhang, Jian; Wang, Yongqiang; Liu, Peng; Hong, Mengqing; Guo, Enkai; Zhong, Fen; Cai, Guangxu; Jiang, Changzhong; Ren, Feng
Abstract: Finding high performance plasma-facing materials (PFMs) is one of the most important and challenging tasks for realizing the commercial application of fusion reactors. Herein, we found the CrMoTaWV high entropy alloy (HEA) is highly resistant to low-energy and high-flux He plasma exposure. The nanochannel HEA film has 20 times higher initial fluence for the formation of fuzz and a remarkable 8.9 times slower fuzz growth rate than those of W. Combining the in-situ TEM observation and the Molecular dynamics (MD) simulation of the He bubble growth process, a new mechanism for the enhanced radiation resistance in HEA with the unusual interaction between HEA and He is found, where, differing from traditional metal, bubble growth in HEA leads to non-directional emission of interstitial atoms while HEA greatly suppress the growth of He bubbles. The special nanochannel structure further rise the radiation resistance through releasing He out of the HEA film and reducing the He concentration. This new nanochannel refractory HEA material presents a promising choice as the PFMs with excellent performance and a much longer serving lifetime for future commercial fusion reactors. Graphical abstract: Image, graphical abstract